Capillitial extrusion from fruits of Maxillaria nardoides (Orchidaceae: Maxillariinae) - Blanco Coto, Mario Alberto (2006)
The fruits of Maxillaria nardoides are fusiform, 1–1.2 × 0.3 cm. Upon dehiscence, six valves separate completely at the apex, and a long cylindric mass (up to 6.5 cm long × 3 mm in diameter) of white hygroscopic trichomes (elaters) is extruded along with the seeds. This capillitium hangs limply from the fruit with its base clamped by the three placentiferous valves that fold longitudinally upon dehiscence. The seeds are forcefully ejected from the capillitium as the elaters unwind and recoil. This long extrudable capillitium appears to be unique among the Orchidaceae. Its potential adaptive value is discussed.